Neuroimaging in the Emergency Department for Patients with Symptoms of Vitreoretinal Traction - Malick, Adnan; Belin, Peter J.; Deramo, Vincent; Winokur, Jules; Gorski, Matthew; Pantic, Dorjan; Schloss, Evan R.; Fastenberg, David (Journal of Academic Ophthalmology, 2019)
Eye conditions result in 2.4 million emergency department (ED) visits annually. The purpose of this study is to investigate the management of patients with symptoms of vitreoretinal traction. Retrospective observational study was performed in three Northwell Health EDs between January 2014 and January 2017. Patients with monocular flashes, floaters, or changes in visual field for whom ophthalmology were consulted. Ninety-six patients were included (45 female), mean age 58.4 years. Complaints included floaters in 47 (49%), visual field changes in 39 (41%), and flashes in 28 (29%). Eighteen patients (19%) presented with more than one symptom. Of 24 patients with documented eye examinations by emergency physicians, 10 included confrontational visual fields (CVF). Before ophthalmology consultation, tests included blood work in 29 patients (30%), computerized axial tomography (CT) head in 33 (34%), orbit ultrasound in two (2%), magnetic resonance imaging (MRI) head in 1one (1%), and erythrocyte sedimentation rate (ESR)/C-reactive protein (CRP) in one (1%). Diagnoses by ophthalmologists were posterior vitreous detachment in 44 patients (46%), vitreous hemorrhage in 31 (32%), retinal detachment or tears in 12 (13%), central retinal artery occlusion in six (6%), and central or branch retinal vein occlusions in three (3%). Of 12 patients with retinal detachments or tears, 5 (42%) underwent surgery within 1 week. In patients presenting to the ED with symptoms of vitreoretinal traction, over 30% underwent imaging and blood work before ophthalmology consultation. Signs and symptoms of retinal pathology should be recognized promptly. Triaging, focused examination, and a detailed history may lead to fewer imaging studies and more cost savings.
Keywords: diagnostic imaging; visual complaints; management; ophthalmology